Multichannel matching pursuit validation and clustering—A simulation and empirical study - Lelic, Dina; Gratkowski, Maciej; Hennings, Kristian; Drewes, Asbjørn Mohr (Journal of neuroscience methods, 2011)
▶ MMP accuracy decreases as the number of brain sources increases. ▶ MMP is robust to noise. ▶ We propose a modified K-means clustering to automate MMP analysis. Multichannel matching pursuit (MMP) is a relatively new method that can be applied to electroencephalogram (EEG) signals in combination with inverse modelling. However, limitations of MMP have not been adequately tested. The aims of this study were to investigate how the accuracy of MMP algorithm is altered due to increased number of brain sources and increased noise level, and to implement and test a modified K-means clustering algorithm in order to group similar MMP atoms in time–frequency and space between subjects together. Four groups of 20 EEG signals were simulated. The groups consisted of simulations with 5, 10, 15, and 20 brain sources. The accuracy of MMP algorithm was first tested on increasing number of sources. Then, different levels of noise were added to the simulations and accuracy of the algorithm was tested on increasing noise level. K-means clustering algorithm was tested on 4 datasets (5, 10, 15, and 20 sources) of 10 similar phantom subjects. Finally, the clustering algorithm was tested on empirical somatosensory evoked potential and brainstem evoked potential data. The MMP accuracy decreased as the number of sources increased and MMP accuracy was robust to noise. Furthermore, we found that when applying the clustering method to a subject group's MMP data, the clustering method grouped the similar atoms between subjects correctly. The MMP and clustering method proved to be an efficient way to group similar brain activity and thus study differences in brain activation sequence to sensory stimulation between groups of subjects.